A Thyroglossal Tumor-Like Lesion on the Tongue: A Case Report - Fatemeh Owlia; Yasaman Sabaghzadegan (Mashhad University of Medical Sciences, 2023)
Background: Pyogenic granuloma is a benign and non-neoplastic mucocutaneous lesion that has multiple causes and develops in response to local irritation, trauma, or hormonal changes during pregnancy. In the oral cavity, this lesion often involves the anterior of the maxillary gingiva, and rarely, the tongue, labial mucosa, and palatal mucosa are involved. The clinical appearance of the lesion was usually seen as a nodule with or without a base, with a smooth surface or lobulated surface. It is usually non-tender, but it can bleed on touch. This lesion may be seen in any size from a few millimeters up to several centimeters. It is more common in females. This case report presents a rare site of a pyogenic granuloma on the dorsal site of the tongue. Clinical symptoms, causes, differential diagnosis, histology of the pyogenic granuloma, and treatment were discussed in this case report.